2022
DOI: 10.51847/knev4spshf
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxıcıty in Patıents on Tenofovır vs Non-Tenofovır Contaınıng Art Regımen: An Observatıonal Study

Abstract: Treatment of Human Immunodeficiency Virus (HIV) infection has been revolutionized by the newer generation of Anti-Retroviral therapy (ART). The first-line ART comprises of NRTI (Tenofovir plus Lamivudine) and one NNRT, Efavirenz. The renal tubular dysfunction associated with Tenofovir is an adverse effect of concern. This study was undertaken to find the incidence of nephrotoxicity due to Tenofovir based regimen in comparison to non TLE regimen. A nonrandomised cross-sectional study with 50 patients between 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…In contrast to other studies, Agrawal et al [ 18 ] found that patients who experienced nephrotoxicity were not underweight, and age was not a factor either, unlike in earlier studies where advanced age was an independent risk factor. They never discovered an association between the mean CD4 count of patients in both groups and the development of nephrotoxicity (500-1,500 cells/mm 3 ) because all the patients in both groups had below-normal CD4 counts.…”
Section: Reviewmentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast to other studies, Agrawal et al [ 18 ] found that patients who experienced nephrotoxicity were not underweight, and age was not a factor either, unlike in earlier studies where advanced age was an independent risk factor. They never discovered an association between the mean CD4 count of patients in both groups and the development of nephrotoxicity (500-1,500 cells/mm 3 ) because all the patients in both groups had below-normal CD4 counts.…”
Section: Reviewmentioning
confidence: 71%
“…14.3% of the 27% of proteinuria patients who had renal impairment also had proteinuria. However, the prevalence of glycosuria at the end of six months remained constant with the baseline frequency Renal impairment was identified in one-fourth of the individuals in this trial, raising concerns about the long-term use of TDF Agrawal et al 2022 [18] Serum creatinine levels at baseline and during the study period indicated a positive correlation (0.233) with a significant correlation and dependence (0.020) for all 100 patients when comparing the TLE with the non-TLE-based regimens. Baseline serum creatinine and at the time of the study were somewhat correlated (0.574) for the TLE regimen, and the association was both significant (0.000) and dependent (0.001).…”
Section: Conclusion About Tdf Relationmentioning
confidence: 78%